2017
DOI: 10.1099/jmmcr.0.005092
|View full text |Cite
|
Sign up to set email alerts
|

A case of polymicrobial anaerobic spondylodiscitis due to Parvimonas micra and Fusobacterium nucleatum

Abstract: Introduction. Here, we present a case of polymicrobial anaerobic spondylodiscitis. Case Presentation. A forty-five year-old female patient was referred to a specialist orthopaedic hospital with an eight week history of back pain without fevers. X-ray imaging and magnetic resonance imaging showed acute osteomyelitis of the twelfth thoracic and first lumbar vertebrae. Prolonged enrichment cultures grew Parvimonas micra and Fusobacterium nucleatum, identified by matrix-assisted laser desorption ionisation-time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…There are few reports on pyogenic spondylitis [ 3 ] and septic arthritis of the knee [ 4 ]; however, there are no reports on P. micra causing osteomyelitis in the fingers. On the other hand, there are several reports on the occurrence of osteomyelitis in the spine [ 5 ] and long bones [ 6 ]; however, there are no reports on the occurrence of finger osteomyelitis due to F. nucleatum . This is the first report on osteomyelitis of the finger bone caused by P. micra and F. nucleatum, which is probably related to the treatment of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on pyogenic spondylitis [ 3 ] and septic arthritis of the knee [ 4 ]; however, there are no reports on P. micra causing osteomyelitis in the fingers. On the other hand, there are several reports on the occurrence of osteomyelitis in the spine [ 5 ] and long bones [ 6 ]; however, there are no reports on the occurrence of finger osteomyelitis due to F. nucleatum . This is the first report on osteomyelitis of the finger bone caused by P. micra and F. nucleatum, which is probably related to the treatment of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic culture remained negative while anaerobic culture yielded P. micra and F. nucleatum. Polymicrobial anaerobic infection with P. micra and F. nucleatum is a rare finding in bone and joint infections, except for a case of spondylodiscitis reported by Cleaver et al [13]. Elevated counts of white blood cells in synovial fluid have little significance in the diagnosis of septic arthritis; however, in the present case, the procedure could not be performed in the presence of necrotic cells.…”
Section: Discussionmentioning
confidence: 51%
“…Cobo et al reported that P. micra infections were diagnosed on the basis of infected fluids in 38.7% of cases, blood cultures in 29%, and molecular techniques in 22.5% [5]. In recent times, as new methods (e.g., 16S ribosomal RNA sequencing [3], matrix-assisted laser desorption ionization time-of-flight mass spectrometry [4], and melting temperature mapping [16]) have become more available in routine diagnostic laboratories, P. micra has been increasingly detected in various invasive human infections.…”
Section: Discussionmentioning
confidence: 99%